Scanless terahertz imaging in the time domain - Zanotto, Luca; Balistreri, Giacomo; Rovere, Andrea; Kwon, O. Pil; Morandotti, Roberto; Piccoli, Riccardo; Razzari, Luca (2023 Photonics North, PN 2023, 2023)
We realize scanless time-domain imaging at terahertz frequencies, by combining a single-pixel imaging scheme with a 'single-shot' detection method. We also apply compressed sensing to further speed up the acquisition process.
Keywords: Compressed-Sensing; Scanless; Scanless acquisition; Single pixel; Tera Hertz; Terahertz frequencies; Terahertz imaging; Terahertz multidimensional imaging; Time domain; Time-domain imaging; compressed sensing; scanless acquisition; Terahertz multidimensional imaging